PREDICTING CORPORATE TURNAROUND USING LOGISTIC REGRESSION ANALYSIS: A RESEARCH ON BURSA MALAYSIA COMPANIES - Tengku Mohammad Chairal Abdullah; Zolkafli Hussin (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2010)
There has been considerable research done by academicians and practitioners on corporate bankruptcy predictions, though in the field of corporate turnaround such research were somehow much lacking. Scholars argued that early acceptance of turnaround situation were important for successful recovery. Therefore early predictions on turnaround situation were much needed. This paper seeks to give an overview of corporate turnaround predictions. The samples were taken from the main board companies of Bursa Malaysia from the year 1997 to 2005. Data were taken from financial statement which being published in the Handbook of Annual Report. Several financial ratios were considered in the analysis to see whether a significant difference exists between Turnaround and Non-Turnaround firms. The research used Logistic Regression Analysis as statistical tool. The study found Financial Leverage Ratio (Total Debt/Total Asset), Sales/Total Asset, Receivables/Inventory and Total Tangible Asset to have statistical significant measure to differentiate between the two groups of companies. The study also found that those ratios could be use as significant predictor variables in measuring the probability of a particular company to fall under one of those categories. Hopefully the findings of the research would shed some light and give a better platform in predicting which company would enter the phase of turnaround situation.